2018
DOI: 10.21106/ijma.217
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Assessment and Maternal Perception of Toddler Body Size using Toddler Silhouette Scale in Nigeria a Developing Country

Abstract: Background and Objectives:The toddler silhouettes scales have been validated in the caucascian population in developing countries but in the African population, the use of these scales is yet to be evaluated. The aim of this study was to determine the perception of mothers on the body size of toddlers using a validated scale in an African population.Methods:This was a cross sectional study of 241 mothers and their toddlers. Study participants were recruited from the immunization and pediatric clinics. The moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(52 reference statements)
1
3
0
Order By: Relevance
“…Mothers in our study were less accurate at assessing their child's weight status than their own, with only half correctly identifying their child's weight. The overall percentage correct in our study was similar to findings from a study in Nigeria, which used the same type of silhouettes, and both studies found that mothers were more likely to underestimate their child's weight status if the child was overweight (Adeniyi et al, 2018). These findings fit the pattern in high‐ and middle‐income countries showing that parents are generally inaccurate at assessing child weight status (Doolen, Alpert, & Miller, 2009; Lundahl et al, 2014; Moffat, 2000) and tend to underestimate the weight status of overweight children (Francescatto et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Mothers in our study were less accurate at assessing their child's weight status than their own, with only half correctly identifying their child's weight. The overall percentage correct in our study was similar to findings from a study in Nigeria, which used the same type of silhouettes, and both studies found that mothers were more likely to underestimate their child's weight status if the child was overweight (Adeniyi et al, 2018). These findings fit the pattern in high‐ and middle‐income countries showing that parents are generally inaccurate at assessing child weight status (Doolen, Alpert, & Miller, 2009; Lundahl et al, 2014; Moffat, 2000) and tend to underestimate the weight status of overweight children (Francescatto et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…We identified only one study of child body size preferences in sub‐Saharan Africa, conducted in Nigeria. It showed that 35% of mothers underestimated and 24% overestimated their child's body size (Adeniyi, Ekure, Olatona, Ajayi, & Nworgu, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean score from each indicator were measured. Mother's satisfaction was assessed using Toddler Silhouette Questionnaire, which consists of 2 sets of 7 children's picture with number 1 (thinnest) to 7 (fattest) 12 . Mother asked to choose picture's number that describe (1) the body size that most closely resembled their child, and (2) the body size that she want their child to be, and score is obtained from the difference set (1) minus set (2).…”
Section: Methodsmentioning
confidence: 99%